The diversity of macroinvertebrates as a bioindicator of water quality in the Amprong River, Kedungkandang District - Dwi Oktavia, Rizky; Wijayanti, Titik; Arifin, As'ad Syamsul; Hindun, Nurmala (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
The Amprong River in Kedungkandang District, Malang City, is facing ecological pressure due to dense residential settlements and inadequate domestic waste management. This study was conducted to assess the diversity of macroinvertebrates and to investigate their role as indicators of water quality. A quantitative descriptive method was employed, with samples collected from three stations (upstream, midstream, and downstream) on both sides of the river. Temperature and pH were recorded as key environmental parameters, and the structure of the macroinvertebrate community was analyzed using the Shannon–Wiener diversity index (H'), the evenness index (E), and Simpson’s dominance index (C). A total of 633 individuals representing 13 species and 8 families were identified. The results revealed moderate diversity in most sampling points, while one site exhibited low diversity and high dominance by Melanoides plicarius, indicating heavy pollution. Variations in species composition and ecological indices between riverbanks were influenced by habitat differences, namely vegetation type, substrate, and waste exposure. Overall, the results suggest that the Amprong River is classified between moderately and heavily polluted, underscoring the importance of enhanced environmental management and adequate waste treatment facilities to support river conservation in urban settings.